Histopathological Features and Leukocyte Infiltration in Mice Lungs Administrated with Pseudomonas aeruginous - Chandra Kanta Bhusal; Majed N. Ali; Lubna Ali Abd Al-Mutalib (World Journal of Experimental Biosciences, 2022)
Pseudomonas aeruginosa isolates have the ability to stimulate the pro-inflammatory immune response in addition to developing the infection. The aim of the present study is to estimate the role of P. aeruginosa in generating inflammation and cell filtration in lung tissue. P. aeruginosa (Pa) was isolated from sputum samples collected from patients suffering from pneumonia. The test mice were given 50 µl of standard inoculum (108 c.f.u) of P. aeruginosa intra-nasal (i.n.). The lungs were harvested at different time intervals (4, 24, 48, 72h) to collect bronchoalveolar lavages for estimation of the total number of leukocytes and to prepare the lung section for histopathological examination. A significant increase in leukocyte infiltration was seen as early as 4 h post-instillation with P. aeruginosa and this elevation was seen up to 72h. The histological images showed acute inflammation in terms of cell infiltration and dilation of small blood vessels and edema. The acute inflammation picture appears up to 72 h post instillation with P. aeruginosa. The study proved that P. aeruginosa generates pro-inflammatory phenomena in the lung tissue and increases leukocyte infiltration. That confirms the role of P. aeruginosa infection in generating immune-pathogenesis phenomena in the lungs of experimental mice post-instillation with this bacterial isolate.
Keywords: Histopathology, Leukocytes, Mice, Pseudomonas aeruginosa.